Title: Removal Of Diethylenetriamine Species And Metal Ions From Effluents With Magnetic Activated Carbon - Kaiwen Liu (International Mineral Processing Congress, 2012)
Activated carbon is widely used in the removal of organic and/or inorganic contaminants from waste water due to its high surface area, porous structure, and specific surface reactivity. However, in practical applications, it is difficult to recover the activated carbon completely by screening or classification. In this project,we prepared a magnetic form of activated carbon (magnetic activated carbon or M-AC) by precipitation of iron oxides on the surface of activated carbon. The M-AC can be easily separated from effluents by applying an external magnetic field, thus it can be recycled and regenerated for reuse. M-AC was characterized by X-ray diffraction (XRD), specific surface area measurement, and scanning electron microscope (SEM).XRD results show that the major phase of coated iron oxides on activated carbon is magnetite (Fe3O4). The specific surface area of activated carbon was found to be reduced after the impregnation of magnetite particles on the surface. The SEM micrograph shows the aggregation of the iron oxides on the surface of activated carbon. M-ACwas found effective in removing DETA (diethylenetriamine) species and metal ions from solutions. Cu (II) with initial concentrations from 5 ppm to25 ppm in solution is removed by more than 99% with the addition of 0.1 wt.%ofM-AC. For the removal of 25 ppm DETA species from solution, an addition of 0.5 wt.% of M-AC is required due to the larger size of the DETA molecule. Moreover, M-AC showed a good loadingproperty for nickel and gold ions from solutions. M-ACshows a better adsorption capacityover activated carbon and its potential applications in carbon-in-pulp for gold leaching and waste water treatment. Keywords: magnetic activated carbon (M-AC),diethylenetriamine (DETA),metal ion,adsorption